El concepto metódico de repetición en la hermeneútica de Martín Heidegger - Di Silvestre, Carlos (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2004)

(untitled)
This research considera the context of occurrence and the phenomenic justification of a fundamental methodical concept in Heidegger’s existential hermeneutic, namely, the concept of repetition. In order to do so, this study analises Heidegger’s critique on the assumptions of the phenomenological method of reflection. This paper also takes into account the different aspects of factic life that are entailed in the framing of the concept of repetition. Finally, this work stresses the methodical hermeneutic relevance of the experience of angst.